2005
DOI: 10.1177/002214650504600302
|View full text |Cite
|
Sign up to set email alerts
|

Race Differentials in Obesity: The Impact of Place

Abstract: This article reveals race differentials in obesity as both an individual-and neighborhood-level phenomena. Using neighborhood-level data from the 1990-1994 National Health Interview Survey, we find that neighborhoods characterized by high proportions of black residents have a greater prevalence of obesity than areas in which the majority of the residents are white. Using individual-level data, we also find that residents of neighborhoods in which at least one-quarter of the residents are black face a 13 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 67 publications
7
139
1
Order By: Relevance
“…Using The Americans' Changing Lives (ACL), Robert and Reither (2004) found that community socioeconomic disadvantage helped explain some of the differences in BMI between Black and White women, above adjustments for individual socioeconomic status. Furthermore, though not a focus in their study, Boardman et al (2005) also found that the BMI difference between Blacks and Whites was attenuated once neighborhood conditions were included in the models. 3 In both studies, substantial differences remained.…”
Section: Neighborhoods Body Mass Index and Ethnicitymentioning
confidence: 90%
See 3 more Smart Citations
“…Using The Americans' Changing Lives (ACL), Robert and Reither (2004) found that community socioeconomic disadvantage helped explain some of the differences in BMI between Black and White women, above adjustments for individual socioeconomic status. Furthermore, though not a focus in their study, Boardman et al (2005) also found that the BMI difference between Blacks and Whites was attenuated once neighborhood conditions were included in the models. 3 In both studies, substantial differences remained.…”
Section: Neighborhoods Body Mass Index and Ethnicitymentioning
confidence: 90%
“…On the other hand, no association between the isolation index and weight was found for Whites. Boardman et al (2005) found neighborhood poverty and obesity prevalence to be independent predictors for being obese. Robert and Reither (2004) found that community socioeconomic disadvantage and community income inequality, as measured by the Gini index, were significantly associated with BMI for women, net of individual socioeconomic adjustments.…”
Section: Neighborhoods Body Mass Index and Obesitymentioning
confidence: 94%
See 2 more Smart Citations
“…Weight status differs across communities and regions. [20][21][22] For example, areas that are poor and more racially segregated have higher average weight status. 10,20 Recent studies also have focused on how regional differences in weight status may be explained by the contextual restaurant environment.…”
Section: Introductionmentioning
confidence: 99%